Effect of superior trunk block on diaphragm function and respiratory parameters after shoulder surgery. Issue 3 (10th January 2022) - Robles, Constantin; Berardone, Nick; Orebaugh, Steven
Abstract : Background: The interscalene brachial plexus block has been used effectively for intraoperative and postoperative analgesia in patients undergoing shoulder surgery, but it is associated with high rates of diaphragmatic dysfunction. Performing the block more distally, at the level of the superior trunk, may reduce the incidence of phrenic nerve palsy. We hypothesized that superior trunk block would result in diaphragmatic paralysis rate of less than 20%. Methods: 30 patients undergoing arthroscopic shoulder surgery received superior trunk block under ultrasound guidance. Measurements of diaphragm excursion were determined with ultrasound prior to the block, 15 min after the block, and postoperatively in phase II of postanesthesia care unit, in conjunction with clinical parameters of respiratory function. Results: 10 patients (33.3%, 95% CI 17.3% to 52.8%) developed complete hemidiaphragmatic paralysis at the postoperative assessment. An additional eight patients (26.7%) developed paresis without paralysis. Of the 18 patients with diaphragm effects, seven (38.9%) reported dyspnea. 83.3% of patients with abnormal diaphragm motion (56.7% of the total sample) had audibly reduced breath sounds on auscultation. Oxygen saturation measurements did not correlate with diaphragm effect and were not significantly reduced by the postoperative assessment. Conclusion: Although injection of local anesthetic at the superior trunk level is associated with less diaphragmatic paralysis compared with traditional interscalene block, a significant portion of patients will continue to have ultrasonographic and clinical evidence of diaphragmatic weakness or paralysis.